2010
DOI: 10.1128/aac.01392-08
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insights about Class 2 Integrons from Experimental and Genomic Epidemiology

Abstract: In order to contribute to the knowledge of the architecture and epidemiology of class 2 integrons, we performed a class 2 integron molecular survey in which we analyzed 726 isolates in two bacterial populations from environmental and nonepidemiologically related clinical samples, respectively, collected from 1982 to 2007. We recovered the intI2 gene from 130 of 726 isolates, most of which were clinical isolates, and only 1 (a psychrophilic Pseudomonas sp.) was from a water sample. Unlike the widespread distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
58
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 36 publications
14
58
2
5
Order By: Relevance
“…The ability of integrons to integrate resistance gene cassettes makes them prime pools for the further dissemination of antibiotic resistance among clinical isolates of gram-negative bacteria, including Enterobacter isolates (13). Our findings indicated that the 41 % of isolated Enterobacter were integron positive, this rate of integron positive in our isolates are similar with published reports that Enterobacter harbors high prevalence of integron class 1, lower class 2 and no class 3 (14)(15)(16). Of course, in study in France a new class 3 integron, In3-5, detected in an Enterobacter cloacae isolate retrieved from a random French hospital effluent sample (17).…”
Section: Discussionsupporting
confidence: 89%
“…The ability of integrons to integrate resistance gene cassettes makes them prime pools for the further dissemination of antibiotic resistance among clinical isolates of gram-negative bacteria, including Enterobacter isolates (13). Our findings indicated that the 41 % of isolated Enterobacter were integron positive, this rate of integron positive in our isolates are similar with published reports that Enterobacter harbors high prevalence of integron class 1, lower class 2 and no class 3 (14)(15)(16). Of course, in study in France a new class 3 integron, In3-5, detected in an Enterobacter cloacae isolate retrieved from a random French hospital effluent sample (17).…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study conducted on 726 isolates, 130 of which harbored class 2 integron and only Acinetobacter baumannii and Enterobacter cloacae strains at a high frequency (Ramírez MS, 2010). In Serratia marcescens, 9 out of 30 (30.0%) were positive for class 2 integron, with identical dfrA1-sat1-aadA1 cassette arrays (Crowley, 2008).…”
Section: Class 2 Integronmentioning
confidence: 94%
“…It is therefore not surprising that their cassette arrays are highly conserved (160) and that their range of cassette functions is much more limited than those of class 1 integrons (161)(162)(163). There are some variant cassette arrays described, and it is thought that these cassette rearrangements were mediated by integrase activity in trans or by suppression of the internal stop codon.…”
Section: Origin Of Class 2 Clinical Integronsmentioning
confidence: 99%